2020
DOI: 10.1037/ccp0000587
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sudden gains before treatment begins: An examination of pretreatment intraindividual variability in symptoms.

Abstract: Objective: Sudden gains during psychotherapy have been found to be predictive of positive treatment outcomes. Previous attempts at predicting occurrence of sudden gains have yielded equivocal findings. Recently, intraindividual variability in symptoms during treatment was suggested as a trans-therapeutic and trans-diagnostic predictor of sudden gains. The goal of the present study was to examine this predictor in Internet-delivered treatment for social anxiety disorder (SAD) and to examine whether this predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 57 publications
5
19
1
Order By: Relevance
“…High inter-rater agreement for a diagnosis of SAD was found between the assessor in the present study and other assessors in a recent published study (Shalom et al, 2020; Kappa = 0.86).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…High inter-rater agreement for a diagnosis of SAD was found between the assessor in the present study and other assessors in a recent published study (Shalom et al, 2020; Kappa = 0.86).…”
supporting
confidence: 77%
“…High inter-rater agreement for a diagnosis of SAD was found between the assessor in the present study and other assessors in a recent published study(Shalom et al, 2020; Kappa = 0.86).3 Four participants indicated that they were attracted to individuals of the same sex and were thus shown pictures of same-sex individuals. However, data from these four participants are not included in the present analysis.4 ROZEN AND ADERKAThis document is copyrighted by the American Psychological Association or one of its allied publishers.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…For these patients, their affect and symptomatology may be relatively malleable or plastic. Supporting this hypothesis, Shalom et al (2020) found that variability in social anxiety symptoms (that include some affective items) before psychotherapy is predictive of sudden gains during the treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Though single-time clinician assessment is still considered the gold standard in psychotherapy practice and research, pre-treatment ecological momentary assessment (EMA) is increasingly being employed to assess clinically relevant factors (e.g., Lutz et al, 2018 ; Rubel et al, 2018 ; Fisher et al, 2019 ; Shalom et al, 2020 ). It allows for intensive repeated measurement of variables of interest and modeling their dynamic inter-relationships (e.g., Fisher and Boswell, 2016 ).…”
Section: Introductionmentioning
confidence: 99%